Devdarubaladi Tail Matra Basti in Janu Sandhigata Vata: A Case Study - Singh, Sanju; Tiwari, V J (International Research Journal of Ayurveda & Yoga, 2022)
Sandhigatavata is the most common form of articular disorder which may begin asymptomatically in 2nd and 3rd decade of life and is extremely common by age of 60. Among all persons by age of 40 have some pathological changes in weight bearing joint which limits their day todays activity. In Sandhigatavata the diseases occur in sandhi i.e. joints and janusandhi i.e. knee is the mostly affected joint in Sandhigatavata. Vata dosha plays the major role in this disease. In this case study effect of Devdarubaladi taila matra basti for 21 days is assessed. The study reports significant relief in subjective parameters like Sandhishoola(joint pain), Sandhishotha(swelling), Sandhigraha(stiffness), Akunchana prasaranjanya vedana(pain during extension and flexion of joint), Sandhisphutana(crepitus).